Desegregation and Black Dropout Rates - Guryan, Jonathan (American Economic Review, 2004)
In 1954 the United States Supreme Court ruled that separate schools for black and white children were “inherently unequal.” This paper studies whether the desegregation plans of the next 30 years benefited black and white students in desegregated school districts. Data from the 1970 and 1980 censuses suggest desegregation plans of the 1970's reduced high school dropout rates of blacks by two to three percentage points during this decade. No significant change is observed among whites. The results are robust to controls for family income, parental education, and state- and region-specific trends, as well as to tests for selective migration.